Immune thrombocytopenia exacerbated by nivolumab in a patient with non-small-cell lung cancer. (2016) - Bagley, Stephen J.; Kosteva, John A.; Evans, Tracey L.; Langer, Corey J.
Abstract: Introduction: Nivolumab is a programmed death 1 (PD-1) immune-checkpoint inhibitor antibody currently approved for second-line therapy of metastatic non-small-cell lung cancer (NSCLC). PD-1 inhibitors including nivolumab are associated with a unique spectrum of immune-related adverse events (irAEs), though hematologic irAEs are rare and have not been previously reported in patients with NSCLC. Presentation of case: Here we report a patient who experienced an exacerbation of underlying immune thrombocytopenia (ITP) while receiving nivolumab for NSCLC. The patient's ITP was successfully managed with romiplostim during nivolumab therapy, allowing for 7 months of clinical benefit and a partial tumor response. Discussion: Using this case as an example, we provide a brief review of irAEs associated with PD-1 blockade, with particular attention to hematologic events. We also describe our approach to the use of nivolumab in this patient with underlying autoimmune disease. Conclusion: Patients with NSCLC and underlying autoimmune disease may experience a flare of the autoimmune condition while receiving immune checkpoint inhibition. As illustrated by this case of ITP exacerbated by nivolumab, careful management of the autoimmune disease may allow for the safe administration of PD-1 directed agents in these patients.